Rekonsiliasi Pemuda dengan Alam - Nency Aprilia Heydemans; Fienny Maria Langi (Jurnal Studi Pemuda, 2019)
The earth is getting hotter. Extreme climate change occurred globally in the era of the industrial revolution 4.0. Global warming is a threat as well as human responsibility as the perpetrators of environmental damage. Waste and population growth threaten the function of ecosystem sustainability. From this issue, arises awareness for young people to reconcile with themselves and nature, through a green lifestyle. Green lifestyle is an effort of the youth to contribute, in order to save the ecology. This study's aim is to determine the sensitivity of the youth of the Evangelical Christian Church in Minahasa (GMIM) to environment, by carrying a tumbler as part of a green lifestyle. This research uses a qualitative method, with a descriptive approach through ecological studies. The data obtained are primary data through observation and in-depth interviews with 4 GMIM youths aged 16-30 years, then secondary data through books, journals, and the internet. The results of this study indicates that the green lifestyle of the youth of GMIM by carrying a tumbler, can reduce plastic waste, which also supports the success of youth reconciliation with nature. Apart from oneself, Minahasa social and cultural factors also play a role in preserving the environment.